Parental Control System Aktivitas Santri Berbasis Android (Studi Kasus : Pondok Pesantren Mahasiswa Baitul Jannah) - Alfauzi, Roiyan Zadana; Poerbaningtyas, Evy; Oktavia, Chaulina Alfianti (LPPM STIKI MALANG, 2019)
The establishment of Baitul Jannah Islamic Boarding School in Malang is a form of implementation in order to produce young people, especially religious and noble students. In an effort to account for Baitul Jannah's Islamic Boarding School for parents of students, the need for a liaison between the board of the cottage and parents in monitoring the activities of students. The importance of a communication forum to reduce information gaps, encourages writers to design the application of Parental Control System on the activities of android-based Baitul Jannah Islamic Boarding School students. In this research, the method used is descriptive qualitative data collection techniques in the form of direct observation in Baitul Jannah Islamic Boarding School, study of literature by studying the existing literature, and interviews directly to parents and the board of teachers. In addition, the design of this application applies the Firebase cloud messaging technology that will send notifications to users. The results of the design and implementation of the application of the parental control system activities of students in the Baitul Jannah Student Islamic Boarding School, found that the application is able to help parents monitor their children's learning activities and development. Based on a questionnaire filled out by 40 respondents about satisfaction, comfort, and convenience in operating the application, it showed 98.5% of opinion if the application had been effective in communication between students, the board of teachers, and parents.